LPS-mediated effects and spatio-temporal expression of TLR2 and TLR4 in the bovine corpus luteum. Issue 4 (April 2016) - Lüttgenau, J; Herzog, K; Strüve, K; Latter, S; Boos, A; Bruckmaier, R M; Bollwein, H; Kowalewski, M P
Abstract : When given intravenously (iv), lipopolysaccharide (LPS) transiently suppresses the structure and function of the bovine corpus luteum (CL). This is associated with increased release of prostaglandin (PG) F2α metabolite. The underlying regulatory mechanisms of this process remain, however, obscure. Therefore, the aims of this study were: i) to investigate the expression of the LPS receptor toll-like receptor 4 ( TLR4 ) and 2 ( TLR2 ) in the bovine CL during early, mid- and late luteal phases; and ii) to further dissect the mechanisms of LPS-mediated suppression of luteal function. As revealed by semi-quantitative qPCR and immunohistochemistry, both receptors were detectable throughout the luteal lifespan. Their mRNA levels increased from the early toward the mid-luteal phase; no further changes were observed thereafter. The TLR4 protein seemed more highly represented than TLR2. The cellular localization of TLRs was in blood vessels; weaker signals were observed in luteal cells. Additionally, cows were treated either with LPS (iv, 0.5 μg/kg BW) or with saline on Day 10 after ovulation. Samples were collected 1200 h after treatment and on Day 10 of the respective subsequent (untreated) cycle. The mRNA expression of several possible regulatory factors was investigated, revealing the suppression of PGF2α receptor ( PTGFR ), STAR protein and 3β-hydroxysteroid dehydrogenase, compared with controls and subsequent cycles. The expression of TLR2 and TLR4, interleukin 1α ( IL1A ) and 1β ( IL1B ) and of PGF2α and PGE2 synthases ( HSD20A and mPTGES respectively) was increased. The results demonstrate the presence of TLR2 and TLR4 in the bovine CL, and implicate their possible involvement in the deleterious effects of LPS on its function.